«WHITE» RUSSIA: THE PROBLEM OF CHOICE OF FORMS OF TERRITORIAL ORGANISATION - A. G. Gataullin; D. R. Zainutdinov (Russian Journal of Economics and Law)
Objective: to determine the «white» statehood landmark in choosing the forms of territorial organization of Russia. Methods: the methodological basis of the research is universal dialectic method of cognition, which allows to study the phenomena and processes in their historical development based on scientific (systemic-structural), special (hermeneutics) and private law (comparative and formal legal) methods. Results: basing on the analysis of historical analogues developed and justified in the general theory of law and state, it is proved that the state and legal ideology of «white» statehood has elaborated a direction for the construction of a complex decentralized unitary state, consisting of national-cultural and territorial autonomies. Scientific novelty: the article develops and introduces into scientific circulation the conceptual theoretical and legal provision of regional state as one of the forms of Russia’s territorial organization, selected by «white» modes. The liberal-democratic ideology of «white» statehood in state legal construction facilitated the formation of a unitary decentralized state with wide powers of territorial and national-cultural autonomies. Centralization of power was necessary to eliminate the country's collapse. In the late period of «white» statehood (rule of P. N. Wrangel) it was supposed to build the regional state with a strong decentralization of power. Practical value: the provisions and conclusions can be taken into account (referring to the historical experience) for the state-legal ideology formation, in case it is necessary to increase the role and influence of society in the legal and political life of the country. The research results can be used in the preparation of courses, textbooks and educational-methodical manuals, programs of the theory of state and law, history of state and law, history of political and legal doctrines and also general courses on politics and history of Russia of XX century.